MODEL PEMBELAJARAN KOOPERATIF QUESTION STUDENT HAVE (QSH) UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA KELAS XI SMAN 5 PEKANBARU - Chadmelia Igga Mustika; Erviyenni '; Maria Erna (Jurnal Pendidikan Kimia Universitas Riau, 2016)
The implementation of cooperative learning model Question Student Have been implemented in Class XI SMAN 5 Pekanbaru aims to increase the activity and student achievement on the subject of the solubility and solubility product. This study is experimental with pretest-posttest design. The research sample consisted of grade XI IPA 4 as an experiment and as a class XI IPA 6 controls were randomly selected from two classes homogeneous. Applied experimental class of cooperative learning model Question Student Have whereas the control class without the application of the cooperative model Question Student Have. Data collection techniques use the observation sheet and test Based on observations of classroom learning activities has conducted experiments during the process of learning activities in accordance with the model applied and obtained tcount > t table (2.258> 1.67) means the implementation of cooperative learning models Question Student Have can improve student achievement on the subject of solubility and product solubility in class XI SMA 5 Pekanbaru, with an increase of 6.53%.Keywords: cooperative Question Student Have, activity and Learning Achievemen